Regulation of Intestinal Stem Cell Stemness by the Aryl Hydrocarbon Receptor and Its Ligands - Wisniewski, Paul J.; Nagarkatti, Mitzi; Nagarkatti, Prakash S. (Frontiers in Immunology, 2021)
Maintenance of intestinal homeostasis requires the integration of immunological and molecular processes together with environmental, diet, metabolic and microbial cues. Key to this homeostasis is the proper functioning of epithelial cells originating from intestinal stem cells (ISCs). While local factors and numerous molecular pathways govern the ISC niche, the conduit through which these processes work in concordance is the aryl hydrocarbon receptor (AhR), a ligand-activated transcription factor, whose role in immunoregulation is critical at barrier surfaces. In this review, we discuss how AhR signaling is emerging as one of the critical regulators of molecular pathways involved in epithelial cell renewal. In addition, we examine the putative contribution of specific AhR ligands to ISC stemness and epithelial cell fate.